The Belanger Tradition of the Sasak People: An Ethnoscientific Study of Cultural, Chemical, and Ecological Dimensions - Al Idrus, Syarifah Wahidah; Rahmawati, Rahmawati; Nurhidayatullah, Nurhidayatullah (Jurnal Pijar Mipa, 2025)
The Belanger tradition is an indigenous Sasak hair-cleansing practice that integrates cultural values, ethnochemical knowledge, and environmental sustainability. This study investigates the Belanger tradition, a Sasak hair-cleansing ritual utilizing natural ingredients such as coconut milk, hibiscus leaves, and kaffir lime. Employing a qualitative ethnochemical approach, data were collected through in-depth interviews, participatory observation, and documentation at three sites in Lombok. The findings reveal that Belanger transcends mere physical hair treatment; it embodies a holistic practice of physical and spiritual purification, reinforced by its socio-cultural role in strengthening community bonds and intergenerational knowledge transmission. Scientific analysis demonstrates that the selected ingredients possess bioactive properties with clear ethnochemical rationales. Coconut milk, rich in lauric acid, provides conditioning and antimicrobial benefits. Kaffir lime offers essential oils and flavonoids with antifungal and antioxidant activities, while hibiscus leaves contribute natural saponins for gentle cleansing. The traditional practice of roasting coconut further enhances its adsorptive capacity through mild pyrolysis. Environmentally, the tradition exemplifies a sustainable model, as all materials are biodegradable and locally sourced, in contrast to the persistent chemical waste associated with synthetic shampoos. Thus, this research concludes that Belanger represents a significant convergence of indigenous wisdom and empirical science. It serves not only as a cultural heritage but also as a viable case study for sustainable cosmetic practices and context-based science education, highlighting the relevance of local knowledge in contemporary discourses on health, ecology, and cultural preservation.